2022
DOI: 10.1002/hsr2.946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on reproductive, maternal, newborn, and child health care services in Phuentsholing General Hospital: A retrospective descriptive study

Abstract: Background COVID‐19 pandemic has derailed health care services. The health resources and manpower were prioritized and diverted to curb the COVID‐19 infections at the cost of routine medical services to the people. The impact of the COVID‐19 pandemic on maternal and child health is unknown. This study aimed to assess the impact of the Covid‐19 pandemic on maternal and child health care services in Phuentsholing General Hospital. Methods A descriptive retrospective study was conducted at Phuentsholing General H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Contrarily, studies in Pakistan, Ghana and Sierra Leone identified a greater reduction in doses given at the start of the childhood schedule and attributed this as due to a reduction in births in hospitals [ 26 , 43 , 46 , 48 ]. Dorjey et al [ 30 ] identified an overall drop of in-hospital deliveries of 16% in pandemic years in Bhutan. Kissi et al [ 44 ] reported in Ghana that, prior to COVID-19, “children delivered by traditional birth attendants outside the healthcare sector are more likely to miss immunization because their mothers become hesitant to immunize their children.” COVID-19-related disruption and fewer in-hospital births may combine to hinder EPI coverage due to a relative reduction of healthcare contact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, studies in Pakistan, Ghana and Sierra Leone identified a greater reduction in doses given at the start of the childhood schedule and attributed this as due to a reduction in births in hospitals [ 26 , 43 , 46 , 48 ]. Dorjey et al [ 30 ] identified an overall drop of in-hospital deliveries of 16% in pandemic years in Bhutan. Kissi et al [ 44 ] reported in Ghana that, prior to COVID-19, “children delivered by traditional birth attendants outside the healthcare sector are more likely to miss immunization because their mothers become hesitant to immunize their children.” COVID-19-related disruption and fewer in-hospital births may combine to hinder EPI coverage due to a relative reduction of healthcare contact.…”
Section: Resultsmentioning
confidence: 99%
“…[63] "Reports for seven (23%) of 30 countries indicated challenges with vaccine supply" [21] Lockdowns 14 "Immunisation of new-borns were temporarily deferred in Bhutan during nationwide lockdown periods." [30] "Reduced urban vaccination because needed public transport [to access vaccination centre], which was cancelled due to COVID." [48] "Ban on interstate movement reduced access to healthcare facilities."…”
Section: Measles Disease Outbreaksmentioning
confidence: 99%
“…For instance, early on in the pandemic, volumes of emergency surgery were reduced to lockdowns, elective surgeries, and outpatient appointments were canceled followed by delays ( 124 ). At the Phuentsholing General Hospital in Bhutan, cesarean section deliveries dropped by 6.6% and gynecological surgeries dropped to 13.9% of the total gynecological services from 20.6% during the pandemic years (2020–21) compared to 2019 ( 125 ). Across cancer, cardiovascular, respiratory, and other conditions, surgical treatments during COVID-19 (2020–21) were reduced by 4 to 97% across different studies for India compared to 2019 and previous years ( 126 ).…”
Section: Current Challengesmentioning
confidence: 99%
“…Evidence from past crises, such as the 1997 East Asian financial crisis, the 2008 global financial and food price increase crises, and the 2013-16 Ebola outbreak in West Africa, underscore the vulnerability of women and children, through reduced access to antenatal care, immunizations and schooling [5][6][7][8][9][10]. Evidence from the COVID-19 pandemic paints a similar picture, including deferral or non-receipt of antenatal care visits due to lockdowns and lack of transport, decrease in facility-based deliveries, and child growth monitoring and immunizations by up to 50%, especially in the early months of the pandemic [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%